THE SOCIO-HISTORICAL AND TECHNOLOGICAL CONDITIONS OF THE ORIGIN OF THE SCIENCE FICTION GENRE (Филолошки студии, 2021)
The science fiction genre in all types of media is often neglected in the serious discussion of the scientific public. According to the established opinion, its origin is connected with the writings of Jules Verne and Herbert George Wells at the end of the 19th century, and it is often not seriously analyzed from the perspective of social influence. However, the science fiction genre arises as a response to the great social changes of industrialization and the development of new technologies, showing the possibilities of development ass well as the new moral, psychological and social problems that accompany technological development. With the advent of film, and especially television, the genre gained in expressive power by dealing with some of the very complex and significant social problems of modern society through the prism of fiction.The aim of the paper is to point out the social conditions of its origin and development through a historical presentation of some of the most significant works of science fiction in literature and film. The paper presents and analyzes the works of Verne, Wells, Asimov, Clarke, Čapek, but also large television and film series such as Star Trek. It has been determined that social circumstances, progress of scientific thought and technology highly influenced the development of this genre.